Basidiobolomycosis of Right Colon Mimicking as Carcinoma of Colon. Issue 5 (14th May 2021) - VS, Vikram; Hallur, Vinay; Samal, Swagatika; Chouhan, Mohd Imran; Bhat, Sunil Jee; Kumar, Pankaj; Mishra, Tushar S.
ABSTRACT: Gastrointestinal basidiobolomycosis (GIB) is a rare fungal infection with limited geographic distribution. However, the incidence of GIB has shown an increasing trend because of globalization and frequent traveling. GIB is commonly seen to mimic gastrointestinal malignancy and other diseases such as intestinal tuberculosis and inflammatory bowel disease. Tissue diagnosis is considered to be the gold standard for differentiating these mycotic lesions from tuberculosis and malignancy with confirmation of species performed by culture or polymerase chain reaction. The diagnosis of GIB should be conjectured in patients with suspicion of malignancy, with an inconclusive biopsy. It seems prudent to proceed with radical excision of mass early because both colonic malignancy and GIB have high mortality if untreated.